2015
DOI: 10.1111/eva.12266
|View full text |Cite
|
Sign up to set email alerts
|

Human mining activity across the ages determines the genetic structure of modern brown trout (Salmo trutta L.) populations

Abstract: Humans have exploited the earth's metal resources for thousands of years leaving behind a legacy of toxic metal contamination and poor water quality. The southwest of England provides a well-defined example, with a rich history of metal mining dating to the Bronze Age. Mine water washout continues to negatively impact water quality across the region where brown trout (Salmo trutta L.) populations exist in both metal-impacted and relatively clean rivers. We used microsatellites to assess the genetic impact of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 103 publications
(154 reference statements)
6
48
0
Order By: Relevance
“…The TRT dataset showed a moderate number of fixed SNPs, and the highest number of polymorphic r80 loci was recovered for n = M −1. This is in accordance with high levels of differentiation between geographically proximate populations of the species, occupying metal‐contaminated and clean rivers (Paris, King & Stevens ). In king penguins, studies have shown low levels of genetic divergence both within (Cristofari et al .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The TRT dataset showed a moderate number of fixed SNPs, and the highest number of polymorphic r80 loci was recovered for n = M −1. This is in accordance with high levels of differentiation between geographically proximate populations of the species, occupying metal‐contaminated and clean rivers (Paris, King & Stevens ). In king penguins, studies have shown low levels of genetic divergence both within (Cristofari et al .…”
Section: Discussionsupporting
confidence: 80%
“…We used three empirical RAD‐seq datasets for analysis, representing a phylogenetically diverse group of organisms (Table ). The first dataset ( TRT ) consists of data from brown trout ( Salmo trutta L.) samples occupying two different environmental niches (Paris, King & Stevens ): clean (8 individuals) and metal‐impacted (8 individuals) sites. The second dataset ( PGN ) is from the king penguin ( Aptenodytes patagonicus), from two different colonies on different archipelagos (Cristofari et al .…”
Section: Methodsmentioning
confidence: 99%
“…; Paris et al . ), although markedly greater than values detected between Atlantic salmon populations in the Tamar catchment (Ellis et al . ).…”
Section: Discussionmentioning
confidence: 59%
“…Jager et al 2001;Morita and Yamamoto 2002). All of them have genetic consequences, for example reduction in effective population size, shift in migration-selection-drift equilibrium and in local adaptations (Meldgaard et al 2003;Faulks et al 2011;Paris et al 2015). A divergence of brown trout populations isolated by dams established as early as middle ages has been found ).…”
Section: Discussionmentioning
confidence: 99%